The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1002/adsc.201500953
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Oxide‐Mediated Cyclization of o‐Haloaryl N‐Tosylhydrazones: Efficient Synthesis of Indazoles

Abstract: An efficient synthesis of indazoles from readily accessible E/Z mixtures of o‐haloaryl N‐tosylhydrazones has been developed. The thermo‐induced isomerization of N‐tosylhydrazones is discussed. A series of valuable indazole derivatives are prepared in good yields, and the method has been successfully applied to the synthesis of the bioactive compounds, lonidamine, AF‐2785, axitinib, YC‐1 and YD‐3.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 57 publications
0
26
0
1
Order By: Relevance
“…In a previous study, the N ‐sulfonyl moiety in the substrates affected the reactivity . Thus the N‐sulfonyl moiety was then examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the N ‐sulfonyl moiety in the substrates affected the reactivity . Thus the N‐sulfonyl moiety was then examined.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Tang et al. reported an elegant thermoinduced isomerization of o ‐haloaryl N ‐tosylhydrazones and Cu 2 O‐mediated cyclization to synthesize 1 H ‐indazoles . Despite the fact that this approach was a great breakthrough to the previous methods, it suffered from the following challenges: 1) high temperature (140 °C) for the isomerization of C=N double bond in hydrazone; 2) stoichiometric amounts of copper loading (Cu 2 O, 0.5 equiv.)…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtly, the synthesis of these heterocycles was aroused lasting concern for synthetic chemists. The well known approaches to gain 1 H ‐indazoles were using hydrazone deriviatives, including but not limited 1) a transition‐metal‐free oxidative C–N coupling of easily accessible hydrazones was developed by Rao and co‐wokers; 2) C–H amination of N ‐acetyl‐hydrazones in the presence of manganese dioxide under microwave was reported by Duan and co‐workers; 3) by employing molecular iodine as the sole oxidant, Chang and co‐wokers developed a divergent intramolecular C−H amination of hydrazones; 4) a cleavable directing group assisted intramolecular C–H amination of hydrazones was developed by Ding and co‐workers; 5) The nickel‐catalyzed cyclization of in situ generated ortho‐chlorobenzophenone hydrazone derivatives, to afford 3‐(hetero)aryl‐1 H ‐indazoles was documented by Stradiotto in 2017 . Limited number of examples showed that 1 H ‐indazoles could also be delivered via a N−N bond formation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamides and indazoles are important building blocks for pharmaceuticals and bioactive compounds. For example, ionidamine is an anticancer drug; YC‐1 is reported to exhibit anticancer activity; YD‐3 is an angiogenic drug; and WXL‐1 is a potent antimicrobial agent, newbouldine and neuro‐transmitter inhibitors (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…For example, ionidamine is an anticancer drug; YC-1 is reported to exhibit anticancer activity; YD-3 is an angiogenic drug; and WXL-1 is a potent antimicrobial agent, newbouldine and neuro-transmitter inhibitors ( Figure 2). [49][50][51] 2 | EXPERIMENTAL…”
Section: Introductionmentioning
confidence: 99%